Kermises and Carnivals: Chromatics of Popular Feasts in Renaissance Netherlands - Kovbasiuk, Stefaniia A. (Actual Problems of Theory and History of Art, 2014)
In this article the chromatic features of kermises and carnivals visualizations in the 16th c. Netherlandish painting are considered. According to the concept of the most well-known historian of color M. Pastoureau, color is primarily a cultural construct, and the artist’s choice of certain color oft en is not accidental. Turning towards the analysis of popular feasts depictions in the Renaissance Netherlands, we will try to answer several questions: what were the dominant colors in the visualization of kermises and carnivals, what was due to the artist’s choice of a particular color, what semantic fi eld had one or another color, how did the colors in the structure of popular culture of the Netherlands function in the 16th c., and, fi nally, what evolution did the chromatics of the popular feasts experience due to the Reformation. We considered three basic colors of kermises and carnivals — blue, yellow, red, and also striped clothing and other iconographical details of the festivities paintings by P. Breugel the Elder, P. Baltens, M. van Cleve, I. Beukelaer, F. Pourbus the Elder, etc. It was noted that at the end of the 16th c. traditional colors of «the world upside-down» — blue, red and yellow began to yield to the dark palette that was obviously due to the reform of the popular culture started by the supporters of Reformation and apologists of the post-Tridentine Catholic Church. This reform led, in our opinion, to the evolution of the kermises and carnivals chromatics when usual festivities colors — blue as the color of intemperance in drink and food, yellow as the color of stupidity and buff oonery, striped clothing — a symbol of «the world upside-down», red, the color of the feasting itself, — cede to black, brown and white.
Keywords: Chromatics; kermis; carnival; popular culture; history of colors